2013
DOI: 10.1111/php.12096
|View full text |Cite
|
Sign up to set email alerts
|

Tryptophan Cluster Protects Human γD‐Crystallin from Ultraviolet Radiation‐Induced Photoaggregation In Vitro

Abstract: Exposure to ultraviolet radiation (UVR) is a significant risk factor for age-related cataract, a disease of the human lens and the most prevalent cause of blindness in the world. Cataract pathology involves protein misfolding and aggregation of the primary proteins of the lens, the crystallins. Human γD-crystallin (HγD-Crys) is a major γ-crystallin in the nucleus of the human lens. We report here analysis of UVR-induced damage to HγD-Crys in vitro. Irradiation of solutions of recombinant HγD-Crys with UVA/UVB … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
71
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 52 publications
(74 reference statements)
3
71
0
Order By: Relevance
“…The W42R mutation was recently reported to cause hereditary cataract (27), suggesting a mechanistic convergence between genetic and sporadic forms of cataract disease. We found that the W42Q mutant is monomeric and folded in storage, but at high concentrations at 37°C it forms aggregates morphologically similar to those previously obtained by UV-B irradiation (28).…”
supporting
confidence: 68%
“…The W42R mutation was recently reported to cause hereditary cataract (27), suggesting a mechanistic convergence between genetic and sporadic forms of cataract disease. We found that the W42Q mutant is monomeric and folded in storage, but at high concentrations at 37°C it forms aggregates morphologically similar to those previously obtained by UV-B irradiation (28).…”
supporting
confidence: 68%
“…Its pathology has multiple contributing factors, including exposure to UV light, tobacco, and certain specific chemicals; however, the effect is generally the sameaggregation of the eye lens crystallins (5,13,16,17,60,61). In line with the multiple causality of the disease, several distinct biochemical perturbations in vitro have been shown to cause crystallin aggregation (54,(62)(63)(64). Cataract-associated point mutations, especially ones mimicking in vivo chemical modifications, have been highly useful in dissecting the mechanism of aggregation (21,39,51) and developing interventions to modify it (65).…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, in γS, the trps are in positions 47, 73, 137 and 163. How these trp and tyr/cys clusters go to stabilize and protect γ-crystallin has recently been studied [42,43]. Interestingly replacement of even one of these, namely W43 (by R) is seen to lead to weakening of the stability, loss of solubility and protein aggregation in human γD-crystallin, as in the case of a human patient with cataract [44].…”
Section: Section I: Thementioning
confidence: 96%